Phosphorylation of the RNA polymerase II largest subunit during Xenopus laevis oocyte maturation. - Bellier, S (1997)
Xenopus laevis oogenesis is characterized by an active transcription which ceases abruptly upon maturation. To survey changes in the characteristics of the transcriptional machinery which might contribute to this transcriptional arrest, the phosphorylation status of the RNA polymerase II largest subunit (RPB1 subunit) was analyzed during oocyte maturation. We found that the RPB1 subunit accumulates in large quantities from previtellogenic early diplotene oocytes up to fully grown oocytes. The C-terminal domain (CTD) of the RPB1 subunit was essentially hypophosphorylated in growing oocytes from Dumont stage IV to stage VI. Upon maturation, the proportion of hyperphosphorylated RPB1 subunits increased dramatically and abruptly. The hyperphosphorylated RPB1 subunits were dephosphorylated within 1 h after fertilization or heat shock of the matured oocytes. Extracts from metaphase II-arrested oocytes showed a much stronger CTD kinase activity than extracts from prophase stage VI oocytes. Most of this kinase activity was attributed to the activated Xp42 mitogen-activated protein (MAP) kinase, a MAP kinase of the ERK type. Making use of artificial maturation of the stage VI oocyte through microinjection of a recombinant stable cyclin B1, we observed a parallel activation of Xp42 MAP kinase and phosphorylation of RPB1. Both events required protein synthesis, which demonstrated that activation of p34(cdc2)off kinase was insufficient to phosphorylate RPB1 ex vivo and was consistent with a contribution of the Xp42 MAP kinase to RPB1 subunit phosphorylation. These results further support the possibility that the largest RNA polymerase II subunit is a substrate of the ERK-type MAP kinases during oocyte maturation, as previously proposed during stress or growth factor stimulation of mammalian cells.